AUGMENTED REALITY-BASED FLASHCARDS TO IMPROVE SENIOR HIGH SCHOOL STUDENTS’ VISUAL INTELLIGENCE IN CHEMISTRY LEARNING - Sri Puji Ria Nadila; Kusumawati Dwiningsih (JURNAL EDUSCIENCE, 2026)
Purpose – Developing augmented reality-based flashcards to improve students' visual intelligence on covalent bonds in a valid, practical, and effective manner.Methodology – This research employed a Research and Development (R&D) approach, utilising the ADDIE (Analyse, Design, Development, Implementation, and Evaluation) model. Data collection was conducted using validation sheets, student response questionnaires, student activity observation sheets, and visual intelligence pre-test and post-test sheets. Validity was assessed using expert judgment and analyzed descriptively using the median value. Practicality was analyzed descriptively, while effectiveness was examined using SPSS, including paired-samples t-tests and N-Gain. Findings – The study results indicated that the augmented reality-based flashcards for improving students' visual intelligence in the submaterial of covalent bonds are deemed feasible for application based on expert judgment, with a median validation score of 4, which falls within the valid category. The augmented reality-based flashcards were declared practical, with an average score of 90.04% in the convenient category. The media was also found to be effective, as the paired-samples t-test yielded a significance value of 0.000 (<0.05), indicating a significant difference between the students' pre-test and post-test scores, with an N-Gain of 0.79, categorised as high in both pre-test and post-test results.Contribution – This study contributes to chemistry education by integrating augmented reality technology into flashcards developed using visual intelligence indicators as a learning medium that can feasibly improve students' visual intelligence in the sub-material of covalent bonds.